2018
DOI: 10.5551/jat.41731
|View full text |Cite
|
Sign up to set email alerts
|

Low Plasma Levels of Fibroblast Growth Factor-21 in Patients with Peripheral Artery Disease

Abstract: Aim: Fibroblast growth factor-21 (FGF-21) is a metabolic regulator with beneficial effects on glucolipid metabolism. Since FGF-21 has lipid-lowering, anti-inflammatory and anti-oxidant properties, it may play a protective role against atherosclerosis. However, blood FGF-21 levels in coronary artery disease (CAD) or peripheral artery disease (PAD) have not been elucidated.Methods: We measured plasma FGF-21 levels in 417 patients undergoing coronary angiography, who also had ankle-brachial index test for PAD scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…The severity of PAD was classified from stage I to IV according to Fontaine's classification. This study followed the methods of our previous study by Miyazaki et al [ 17 ]. Any patients with a history of percutaneous coronary intervention or cardiac surgery were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…The severity of PAD was classified from stage I to IV according to Fontaine's classification. This study followed the methods of our previous study by Miyazaki et al [ 17 ]. Any patients with a history of percutaneous coronary intervention or cardiac surgery were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…In EAT from T2DM patients with multivessel CAD, FGF-21 gene expression is reduced [ 317 ], and in patients undergoing cardiac surgery, FGF-21 expression in EAT increases after surgery, suggesting a role protecting from surgery-related inflammatory response [ 319 ]. However, several studies have shown that increased levels of circulating FGF-21 are associated with the presence of atherosclerosis [ 337 , 338 , 339 , 340 , 341 ], although there are contradictory results [ 342 ].…”
Section: Role Of Some Adipokines In Inflammatory Processes Associamentioning
confidence: 99%
“…There are also some limitations. Participants were not further stratified into subgroups based on the number of coronary arteries involved or degree of stenosis, however another cross-sectional study found no significant difference in plasma FGF21 levels among CHD patients by numbers of stenosed coronary arteries involved [26]. The present study was a post-hoc analysis of the TNT trial, though all analyses were performed after pre-stating Data are expressed as median (interquartile range).…”
Section: Discussionmentioning
confidence: 97%
“…In rodent models, cardiomyocytes can secrete FGF21 in response to global cardiac ischemia [19]. However, some human studies have shown no associations between FGF21 levels and CVD [25,26]. Nevertheless, these studies are limited by having a cross-sectional design and relatively small sample size (n b 420).…”
Section: Discussionmentioning
confidence: 99%